Overweight and obesity combined with low physical function and non-communicable diseases among older adults in nursing homes represent a group with nutritional risk, malnutrition, and sarcopenia – A cross-sectional pilot study - Tenna Christoffersen; Inge Tetens; Anja Weirsøe Dynesen; Margit Dall Aaslyng; Janne Kunchel Lorenzen; Anne Marie Beck (Clinical Nutrition Open Science)
Background & Aims: Older adults with overweight and obesity (overnutrition) may be overlooked in terms of nutritional risk. The aim of the present study was to characterise older adults in community care with overnutrition according to a proposed screening model and to compare this group with older adults with normal weight in terms of nutritional risk, malnutrition, sarcopenia, or a combination of both. Methods: This cross-sectional pilot study included residents from six nursing homes in a rural Danish municipality. From April to July 2022, we collected data on age, sex, body composition, chronic diseases, muscle strength, nutritional risk and dietary intake from medical records. Nutritional risk, malnutrition and sarcopenia assessments were based on the criteria set in the Eating Validation Scheme, the Global Leadership Initiative on Malnutrition and the European Working Group on Sarcopenia in Older People. A covariate analysis and a Fisher's exact test were used to evaluate differences in the variables and in nutritional risk, malnutrition and sarcopenia between the groups. Results: A total of 116 residents were included in the study. We found that 52% had overnutrition and that 89% of these older adults experienced both low physical function and non-communicable diseases. Compared with older adults with normal weight, the group with overnutrition had a lower calf circumference adjusted for body mass index (P=0.008), a lower 30 second Chair Stand Test score (P=0.03), a higher prevalence of sarcopenia (P=0.02) and a statistically non-significant higher prevalence of malnutrition and sarcopenia combined (P=0.0002). Conclusion: More than half of the older nursing home residents in this study had overnutrition, with almost 90% experiencing both NCDs and low physical function. When comparing the group with overnutrition with older adults with normal weight, the study showed that they had a similar prevalence of nutritional risk and malnutrition and that the prevalence of sarcopenia was higher in those with overnutrition.